Stereotactic body radiotherapy in lung cancer: a contemporary review - Emese Csiki; Emese Csiki; Mihály Simon; Judit Papp; Márton Barabás; Márton Barabás; Johanna Mikáczó; Johanna Mikáczó; Kristóf Gál; David Sipos; Árpád Kovács (Frontiers Media S.A., 2024)
The treatment of early stage non-small cell lung cancer (NSCLC) has improved enormously in the last two decades. Although surgery is not the only choice, lobectomy is still the gold standard treatment type for operable patients. For inoperable patients stereotactic body radiotherapy (SBRT) should be offered, reaching very high local control and overall survival rates. With SBRT we can precisely irradiate small, well-defined lesions with high doses. To select the appropriate fractionation schedule it is important to determine the size, localization and extent of the lung tumor. The introduction of novel and further developed planning (contouring guidelines, diagnostic image application, planning systems) and delivery techniques (motion management, image guided radiotherapy) led to lower rates of side effects and more conformal target volume coverage. The purpose of this study is to summarize the current developments, randomised studies, guidelines about lung SBRT, with emphasis on the possibility of increasing local control and overall rates in "fit," operable patients as well, so SBRT would be eligible in place of surgery.